SOCIAL SUPPORT FOR THE LONG-TERM UNEMPLOYED – PSYCHOTHERAPY SESSIONS - Orska, Rita (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Long-term unemployment causes people to have marked social adaptation problems. All hope to find a job is lost. The person has accepted their status and is hardly looking for a job. Thus, there is no belief that anything could help. Social support for the long-term unemployed provides for a social service – psychotherapy sessions. The understanding that the unemployed have about this service differs. A psychotherapist’sattempts to motivate a client are not always successful. To provide effective social support to the long-term unemployed, complex systemiclong-term help is required, which can be provided by an interdisciplinary team.